2019
DOI: 10.3766/jaaa.17097
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Music Played by Caucasian and Filipino Musicians with and without Conventional and Musicians’ Earplugs

Abstract: Some musicians may play the music louder while using earplugs thus reducing the effectiveness of the hearing protection offered by earplugs. In addition, the dynamic range (DR) of the music may be altered because of the use of earplugs with negative impact on perceived quality of music. There are some cultural differences in attitudes toward loudness, which may lead to differences in the loudness of music played by musicians from different cultures.To investigate the effect of the use of two different types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The results, shown in Figure 4 , indicate that dynamic ranges do not vary significantly across hearing condition. A previous study by Rawool and Buñag (2019) operationalized 2 different measures of dynamic range, namely (max-min) and (max-mean). We therefore replicated the analysis for the second measure of dynamic range and obtained similar results; that is, no effect of hearing condition on either measure of dynamic range was observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results, shown in Figure 4 , indicate that dynamic ranges do not vary significantly across hearing condition. A previous study by Rawool and Buñag (2019) operationalized 2 different measures of dynamic range, namely (max-min) and (max-mean). We therefore replicated the analysis for the second measure of dynamic range and obtained similar results; that is, no effect of hearing condition on either measure of dynamic range was observed.…”
Section: Resultsmentioning
confidence: 99%
“…As previous research (Rawool and Buñag, 2019) had observed an effect of hearing protection on the dynamic range of music performance, we also investigated this phenomenon but found no effect of hearing condition on dynamic range. This could be attributed to two main differences: (1) the instrument types (strings, winds and piano in Rawool and Bunag as opposed to pianists only in this study), (2) the analysis method (audio recording analysis in Rawool and Bunag versus MIDI velocity data in this study).…”
Section: Performancementioning
confidence: 91%
See 2 more Smart Citations